Analysis of Personal Data Security Awareness Level Among Social Media Users Using the Technology Acceptance Model - Aldi Juliansyah; Richky Faizal Amir (International Journal Software Engineering and Computer Science (IJSECS), 2026)
The rapid development of information technology has fundamentally altered communication patterns, most visibly through the widespread adoption of social media as a primary channel for sharing and receiving information. What began as a tool for interpersonal connection has since expanded into a space for commercial activity, personal expression, and mass information exchange — bringing with it a set of risks that deserve more attention than they typically receive. Social media platforms, while offering considerable convenience, carry real threats to personal data security, threats that are too often underestimated by both users and service providers. Personal data routinely spreads across these platforms, sometimes deliberately, more often through carelessness or inattention on either side of the service relationship. The gap between internet penetration rates and actual security awareness among users remains a persistent concern, particularly in developing digital markets where platform adoption has outpaced digital literacy. The present study measured the level of awareness among social media users regarding personal data privacy and security, applying the Technology Acceptance Model (TAM) as the analytical lens. A blended research method was used, combining qualitative and quantitative data collection through a structured questionnaire distributed to 100 randomly selected respondents. The findings indicate a relatively high level of awareness overall: 68.6% of respondents demonstrated awareness of information security practices, while 65.1% showed awareness of personal privacy. These figures are encouraging — though the 15% gap between the two warrants further scrutiny.